"I Would Have Taken This to My Grave, Like Most Women": Reporting Sexual Harassment during the #MeToo movement in India. (26th September 2020) - Sambaraju, Rahul
Abstract: One core concern of workplace sexual harassment is the low rate of reporting, which arguably adds to its suppression and consequent individualization of harassment. The recent #MeToo movements across the globe have been focal points for women to report incidents of sexual harassment. I examined what it has meant for women in India to speak about their experiences of sexual harassment in broadcast media news interviews during the #MeToo movement. Discursive psychological examination showed that interviewers and interviewees (women who were reporting) attended to and managed issues with the perceived legitimacy of reporting sexual harassment. Interviewees had to account for their reporting in the context of the #MeToo movement while managing not to be seen as being swept up by it. Women treated these concerns as gendered phenomena rather than merely interpersonal in justifying their reporting and the #MeToo movement. These findings are discussed in relation to research on silencing of women's voices in reporting, the role of media, and broadly addressing sexism and sexual harassment at the workplace.